Face and content validation of Phacoemulsification techniques related to surgically induced astigmatism questionnaire - Md Mustafa, Md Muziman Syah; Marzuki, Nazaryna; Mohd Kamal, Khairidzan; Ab. Halim, Noorhazayti (2019)
Phacoemulsification surgical techniques are associated with surgically induced astigmatism (SIA) in post-cataract surgery. However, no established tool is currently available to gather information on the surgeon's phacoemulsification techniques. This study aimed to validate a newly developed ‘Phacoemulsification Techniques Related to Surgically Induced Astigmatism’ (PTechSIA) questionnaire. PTechSIA questionnaire was designed to collect information on surgical techniques used by surgeons during phacoemulsification. Questionnaire items were generated based on peer-reviewed literature of related domains to phacoemulsification surgical techniques. The self-administered tool consisted of fifteen close-ended questions. Ten subject-matter experts (SMEs) were recruited for face validation using qualitative approach and content validation using Lawshe’s method. The items in the questionnaire were modified based on feedback from the SMEs. Content validation ratio (CVR) was calculated for each item; items with CVR value of less than 1.00 were eliminated, and the final content validity index (CVI) of the questionnaire was obtained. Out of fifteen items, six items with CVR value of less than 1.00 were eliminated (items number 2, 7, 11, 13, 14, 15) with initial CVI of 0.61. After the modification process, the number of final items was nine, with an overall final CVI score of 1.00. Overall, the finalised PTechSIA questionnaire achieved appropriate validity. Hence, the findings indicate that the PTechSIA questionnaire can be utilized for future assessments of surgical techniques and its association with SIA.